Witchcraft in Russia and Ukraine, 1000-1900 : A Sourcebook - Worobec, Christine D., 1955-; Kivelson, Valerie A. (Valerie Ann) (Book collections on Project MUSE., 2020)
"This book provides the first systematic overview of witchcraft laws and trials in Russia and Ukraine, combining scholarly commentary with primary source materials translated from Polish, Russian, and Ukrainian, most of which have never before been published" --